Fekete-SzegÖ Inequalities for q-Starlike and q-Convex Functions Involving q-Analogue of Ruscheweyh-Type Differential Operator - Soni, Amit; ÇETİNKAYA, ASENA (Palestine Polytechnic University, 2022)
In the present paper, the new generalized Ma-Minda type classes of q-starlike and q-convex functions are introduced by using Ruscheweyh-type q-differential operator. Denote by SRλq (φ) the class of q-starlike functions and CRλq (φ) the class of q-convex functions associated with Ruscheweyh-type q-differential operator, where φ is the function with positive real part. By making use of these classes, we obtain initial coefficient estimates and Fekete-Szegö inequalities for the classes SRλq (φ) and CRλq (φ), respectively. © Palestine Polytechnic University-PPU 2022.
Keywords: Fekete-Szegö Inequality; Q-convex Functions; Q-starlike Functions; Ruscheweyh-type Q-differential Operator